Chiral phonons and pseudoangular momentum in nonsymmorphic systems - Tiantian Zhang; Shuichi Murakami (Physical Review Research, 2022)
Chiral phonons have nonzero polarization and can be observed only via a selective coupling with valley electrons and circularly polarized photons. In such process, a new physical quantity, i.e., pseudoangular momentum (PAM), is required to meet the selection rule. However, phonon PAM was only studied in symmorphic systems with quantized integer values. In this work, we generalized the definition of PAM to systems with screw rotation symmetry, i.e., nonsymmorphic systems, which show distinct properties compared with the one in symmorphic systems: (i) PAM can be nonintegers and q dependent but still be an observable quantity by experiments; (ii) phonon PAM and phonon angular momentum are not equal due the special Wyckoff position in the real space, in contrast to the previous works where most of the atoms are at rotation-invariant Wyckoff positions. Such new definition and discoveries can help us to obtain chiral phonons in a broader class of systems with a nonzero group velocity and to convey information like chirality and angular momentum in solids as expected. Materials are also offered to understand the new definition and for further experimental detection.